Adaptation of Educational Quality Policy: An Implementation Study of Online Learning and Regional Development Implications - Zulkifli Musthan; Faizah Binti Awad; Jalaluddin Rum; Abdul Kadir; Samrin Samrin; Ahmadi Ahmadi; Sarjaniah Zur (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
This study aims to analyze the adaptation of government education policies from the pandemic period in Southeast Sulawesi, which are relevant to the current Regional Development Plan. The focus of this study is on policy implementation, challenges in learning access, and the solutions implemented. The research employs a descriptive qualitative method, with primary data collected through in-depth interviews with key stakeholders in the education sector, including government officials, teachers, principals, educational staff, and students. Secondary data was gathered by examining government policy documents, learning guides, and associated reports. The results suggest that the implementation of learning policies in schools has not achieved complete congruence with national policy regulations. In response, various forms of policy adaptation are implemented at the school level, including modifications to learning strategies and increased parental involvement, which reflect the initiatives of local governments and schools aimed at meeting educational needs. A persistent challenge that has emerged as a primary concern in the execution of regional educational policies concerns the equitable provision of educational opportunities to all students.